Denotations of Resistance in the Palestinian Proverb "Semio-sociological Approach" - Hammad, Mahmud Muhamad; Albarmil, Hasan Abudl Rahman (Journal of Humanities & Social Sciences, 2021)
This study depends on the analysis content by used semio-sociological approach in the interpretation of proverbs through selection of a group of the Palestinian proverbs associated with the resistance dimension. Many studies of proverbs did not address this type of interpretation. Moreover, many of these studies were not up to the desired methodological level because of the proverb’s varied associations with the general life. In its sociological context, the proverb stemmed from a sensory human experience, expressed in simple language. It was able to portray the life of the human through their immersion into the action framework that awakened the collective conscience which rejected the oppressive reality, which drew the differing paths of the proverb and left some margin for explicating the current crisis and how to deal with it. Since the resistant proverb is a part of the cultural landscape, it was in harmony with the novel, poem, drawing and poetry in a revolting image that stressed confrontation as well as rejection of weakness and subjection. It also succeeded in expressing an identity that embodied awareness about the suffering of human reality in all its concise and deep dimensions and historical and social framework. Despite the fact that the proverb is subsumed under the duality of subjection and revolt, the two researchers opted to address the resistant side of it, through a Palestinian model whose space abounds in a movement that bestowed a deep constructivist dimension on the Palestinian landscape. This is parallel with the current objective contexts that the Palestinian society is undergoing. Therefore, this study proceeded along three results, the first results of the interpretive structure of the denotations of the proverb and its projections on the symbols of time and place, secondly the proverb denotations and projections on plantation, animals, the third of the interpretive structure of the denotations of the proverb and its projections on the humans.